If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(2w+5)=3(8-4w)
We move all terms to the left:
-4(2w+5)-(3(8-4w))=0
We add all the numbers together, and all the variables
-4(2w+5)-(3(-4w+8))=0
We multiply parentheses
-8w-(3(-4w+8))-20=0
We calculate terms in parentheses: -(3(-4w+8)), so:We get rid of parentheses
3(-4w+8)
We multiply parentheses
-12w+24
Back to the equation:
-(-12w+24)
-8w+12w-24-20=0
We add all the numbers together, and all the variables
4w-44=0
We move all terms containing w to the left, all other terms to the right
4w=44
w=44/4
w=11
| 1+7n=5n+9 | | (25+x)-(7x-35)=180 | | 2m-1+3m+5m=6m-8 | | 3p/p-5-2/p+3=p/p+3 | | -2x+5x-9=3(x+4)-5 | | z4=12 | | 5(2n–2)=5(23n+10) | | 3−7⋅(3+4x)=-18 | | x/15=22,350 | | -8+9y=8y | | -2(w+2)=4(8-5w) | | n-4=11.25 | | X^2=-18-8x | | 7/5+2/5x=41/20+5/4x+1/4 | | 3j-8=10 | | 11/4+1/9t=4 | | 2x+4=3x–2 | | 1211=12p | | -1/7+y=-3/4 | | 3x+2(x+1)+7=5 | | 3(x+4)=-4(2-2x) | | 2/3y=4-5/6y | | W+9=-2w-8 | | y÷5-4=25 | | 3x+14=6x−1 | | 2x+3+3x=28 | | x-1/3-8=x-1/2 | | 8x+11x=8x+8 | | 10z=8z+45 | | ½y+9=17 | | 5B-3(3b-7)=-11 | | b+5/3=-2 |